Disputed Meanings of Women’s Liberation : Social Tensions and Symbolic Struggles During Angolan Independence - Figueiredo, Fábio Baqueiro; Institute of African Studies; Studies, Bayreuth Academy of Advanced African (University of Bayreuth African Studies Working Papers, 2022)
During the armed struggle, the Popular Movement for the Liberation of Angola (MPLA) supported women's liberation and appointed women to several political, logistical, and military positions. Meanwhile, in colonial society, changes in economic activities, access to formal education, and urban sociability resulted in a more significant female presence in public spaces. After independence, women's liberation rose to prominence in a context of internal conflict and economic disruption. The new government promoted the “New Man” and a host of associated social personae, all of which were defined by a set of moral qualities individuals were expected to comply with if they wanted to qualify as legitimate actors in the making of independent Angola. Women ought to engage in “National Reconstruction” by joining the Organization of Angolan Women (OMA), which focused on literacy and hygienist campaigns aimed at fighting “obscurantism”. However, many urban women had their own agendas, which called for changes in gender roles in both public and domestic realms. This paper seeks to highlight the shifting gender patterns in Luanda and rural guerrilla zones during the late colonial period, and then analyze how, after independence, different groups of women conceived their place in the building of the new nation, and how the State tried to “domesticate” the possibilities of women's activism as such, in symbolic as well as practical ways.
Keywords: Women; women liberation; New Man; Moralities; Gender Relations; Nation Building; Angola